Organizacija in tehnologija izkoriščanja gozdov in njun prispevek v realizaciji možnega poseka v zasebnih gozdovih - Marenče, Jurij (Gozdarski vestnik, 2012)
We are noticing a large gap between feasible and realized cut in private forests. This gap could be reduced by better organization of forest owners and technological modernization of the wood production process. This article deals with forest owners' condition and equipment for forest work, possible directions of forest owners' linking, forest owners' expectations, and their role in intensification of feasible cut. It also estimates the possibilities for using modern technologies, shown in spatial joining of private forest estates and owners' readiness to participate in usage of modern technologies. Finally, possible solutions for modernization and better work in private forests are suggested.
Keywords: zasebni gozdovi; lastniki gozdov; opremljenost; povezovanje; realizacija poseka